Efficiency Strategy for Indonesian Islamic Commercial Banks During the Covid-19 Pandemic - Wisandani, Iwan; Sukmawati, Heni (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Islamic Commercial Banks must be aware of their degree of efficiency to optimize each bank's potential and take advantage of every opportunity. For a bank to succeed, its operations must be efficient; if they are, the value of the business will rise. This investigation used 12 Islamic commercial banks as its subject to assess the level of efficacy of Islamic retail banks in Indonesia. The data analysis method in this study is the Data Envelopment Analysis (DEA) method using the Charnes Chooper and Rhoodes (CCR) model, specifically the Constant Return to Scale (CRS) approach. The two variables employed in this study were used as input and output variables. TPF, Assets, Operational Costs, and Non-Operational Costs are the input variables. The function of funding is the output variable—income from operations and non-operational sources. In addition, a SWOT analysis is conducted based on the findings of the DEA study to determine the strategies used during the Covid-19 pandemic. According to the Input and Output method, two banks have been inefficient for 4 years, and five have changed BUS efficiency from 2015 to 2018. BTPN Syariah, BJB Syariah, Bank Mega Syariah, Bank Syariah Bukopin, Bank Victoria Syariah, and Bank Panin Dubai Syariah are the five (five) banks in question. The average efficiency of Indonesia's Islamic Commercial Banks for that period, from 2015 to 2018, was 91%, which suggests that despite falling short of 100% (excellent).